Analisis Kondisi Kesehatan Mental di Indonesia Dan Strategi Penanganannya - Asa Nur Haryanti; Muhammad Bintang Syah Putra; Nadia Larasati; Vasha Nureel Khairunnisa; Liss Dyah Dewi A (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Mental health is a crucial aspect of achieving holistic health. Globally, around 450 million people suffer from mental and behavioral disorders, with the highest prevalence in India (4.5%). One in four people will experience a mental disorder at least once in their lifetime. If not properly addressed, mental disorders can worsen and pose a burden on families, communities, and governments. This research aims to understand the mental health situation in Indonesia and its mitigation strategies. This study employs an exploratory descriptive analysis by reviewing literature and secondary data. The unit of analysis is the mental health condition in Indonesia. The results of this study indicate that mental health can be improved through effective public health interventions, focusing on prevention and the role of the community in supporting the optimization of individuals' mental functions. The high number of mental health disorder cases and inadequate handling in Indonesia necessitates comprehensive intervention from the government. Necessary steps include supportive policies, funding allocation, access to mental health services, and community-based approaches.